(untitled) (Progressive Agriculture, 2017)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during December 2014 to May 2015 to examine the effect of variety and water management system on the growth and yield performance of boro rice. The experiment consisted of three varieties (cv. BRRI dhan28, BRRI dhan29 and Binadhan-14) and four water management systems (viz. Traditional flooding, non-flooded rice straw mulching, non-flooded water hyacinth mulching and non-flooded no mulching). The experiment was laid out in a split plot design with three replications. Different growth characters, yield and yield contributing characters of boro rice were found to the significantly influenced by variety, water management system and their interactions. At 100 DAT, the highest plant height, maximum number of tillers hill-1, dry matter of shoot hill-1 and dry matter of root hill-1were obtained from BRRI dhan29 and the lowest values were found in Binadhan-14. At 100 DAT, the highest plant height, maximum number of tillers hill-1, dry matter of shoot hill-1 and dry matter of root hill-1 were obtained in non-flooded rice straw mulching treatment and the lowest ones were obtained from non-flooded no mulching treatment. Variety had significant effect on all the crop characters under study except 1000-grain weight. The highest grain yield was obtained from BRRI dhan29 and the lowest value was recorded from Binadhan-14. Water management system was also significantly influenced all crop characters. The highest grain yield was recorded from non-flooded rice straw mulching treatment and the lowest grain yield was found from non-flooded no mulching treatment. The interaction of variety and water management system showed that BRRI dhan29 with non-flooded rice straw mulching resulted in the highest grain yield whereas the lowest yield was observed from the interaction of Binadhan-14 with non-flooded no mulching treatment. The result of the experiment suggests that BRRI dhan29 can be grown economically with non-flooded rice straw mulching treatment. Progressive Agriculture 28 (1): 26-35, 2017